Answer: Y=-1 or Y=-1+4
Step-by-step explanation:
<h3>Use the formula y2- y1 over x2-x1 so it should look like this 1-3 over 3-1 which is -2 over 2 then you divide that which is -1 and if you have to find one all you have to do is use one point label which is x and y so I pick (1,3) so you put 3=-1(1) once you have that you multipy so -1 times 1 is -1 so your gonna add 1 to the -1 and the three the -1 cancel out because it is a zero pair 3+1 is 4 so B=4 </h3>
Answer: It is D
Step-by-step explanation:
Answer:
(a) [8, 14]
(b) ![8 \leq x \leq 14](https://tex.z-dn.net/?f=8%20%5Cleq%20x%20%5Cleq%2014)
(c)See attachment
Step-by-step explanation:
We want to choose a value of x within 3 units of 11.
(a)Now, 11-3=8 and 11+3=14
The possible values of x ranges is in the closed interval [8,14]
(b) Since x is within 3 units of 11., we have:
![|11-x|\leq3](https://tex.z-dn.net/?f=%7C11-x%7C%5Cleq3)
Solving the absolute inequality
![-3 \leq 11-x \leq 3\\$In $ -3 \leq 11-x\\ x \leq 11+3\\x \leq 14\\\\$In $ 11-x \leq 3\\ 11-3 \leq x\\8 \leq x\\$Therefore,an inequality that represents all values of x that meet this constraint is:$\\8 \leq x \leq 14](https://tex.z-dn.net/?f=-3%20%5Cleq%2011-x%20%5Cleq%203%5C%5C%24In%20%24%20-3%20%5Cleq%2011-x%5C%5C%20x%20%5Cleq%2011%2B3%5C%5Cx%20%5Cleq%2014%5C%5C%5C%5C%24In%20%24%2011-x%20%5Cleq%203%5C%5C%2011-3%20%5Cleq%20x%5C%5C8%20%5Cleq%20x%5C%5C%24Therefore%2Can%20inequality%20that%20represents%20all%20values%20of%20x%20that%20meet%20this%20constraint%20is%3A%24%5C%5C8%20%5Cleq%20x%20%5Cleq%2014)
(c)To draw the number line, we use a closed dot since we have the less than or equal to sign.
Answer:
for just the slope its 3/5 or in decimal its .6
Step-by-step explanation:
y's on top x's on bottom
1--2
1+2=3
2--3
2+3=5
so slope is 3/5 or .6
To solve the given equation, w need to review some rules:
![(1) \ ln \ e = 1 \\ (2) \ ln \ b^{a} = a*ln \ b \\ (3) \ ln \ a + ln \ b = ln \ (ab) \\ (4) \ ln \ a - ln \ b = ln \ \frac{a}{b} \\](https://tex.z-dn.net/?f=%281%29%20%5C%20ln%20%5C%20e%20%3D%201%20%5C%5C%20%0A%282%29%20%5C%20ln%20%5C%20%20b%5E%7Ba%7D%20%3D%20a%2Aln%20%5C%20b%20%5C%5C%0A%283%29%20%5C%20ln%20%5C%20a%20%2B%20ln%20%5C%20b%20%3D%20ln%20%5C%20%28ab%29%20%5C%5C%0A%284%29%20%5C%20ln%20%5C%20a%20-%20ln%20%5C%20b%20%3D%20ln%20%5C%20%20%5Cfrac%7Ba%7D%7Bb%7D%20%20%5C%5C)
The given equation is :
![ln \ e^{ln \ x} + ln \ e^{ln \ x^{2}} = 2 \ ln \ 8](https://tex.z-dn.net/?f=ln%20%5C%20%20e%5E%7Bln%20%5C%20x%7D%20%2B%20ln%20%5C%20%20e%5E%7Bln%20%5C%20%20x%5E%7B2%7D%7D%20%3D%202%20%5C%20ln%20%5C%208)
![ln \ x * ln \ e + ln \ x^{2} * ln \ e = 2 \ ln \ 8](https://tex.z-dn.net/?f=ln%20%5C%20x%20%2A%20ln%20%5C%20e%20%2B%20ln%20%5C%20%20x%5E%7B2%7D%20%2A%20ln%20%5C%20e%20%3D%202%20%5C%20ln%20%5C%208%20)
⇒⇒⇒⇒ rule (2)
![ln \ x + ln \ x^{2} = ln \ 8^{2}](https://tex.z-dn.net/?f=ln%20%5C%20x%20%2B%20ln%20%5C%20%20x%5E%7B2%7D%20%3D%20ln%20%5C%20%208%5E%7B2%7D%20)
⇒⇒⇒⇒ rule (1) and rule (2)
![ln \ ( x* x^{2} ) = ln \ 64](https://tex.z-dn.net/?f=ln%20%5C%20%28%20x%2A%20%20x%5E%7B2%7D%20%29%20%3D%20ln%20%5C%2064)
⇒⇒⇒⇒ rule (3)
removing the nature logarithm from both sides
![x^{3} = 64 = 4^{3}](https://tex.z-dn.net/?f=%20x%5E%7B3%7D%20%3D%2064%20%3D%20%204%5E%7B3%7D%20%20)
∴ x = 4
So, the correct answer is option (2) ⇒⇒⇒⇒ x = 4